Sex Differences in Cardiovascular Outcomes of Intravascular Imaging-Guided PCI - Chidubem Ezenna, MD, BS; Sammudeen Ibrahim, MD; Prasana Ramesh, MD; Mahmoud Ismayl, MBBS; Mrinal Murali Krishna, MBBS; Meghna Joseph, MBBS; Kuan-Yu Chi, MD; S. Elissa Altin, MD; Michael G. Nanna, MD, MHS; Andrew M. Goldsweig, MD, MS (JACC: Advances)
Background: Disparities in cardiovascular disease presentation and outcomes between men and women are well-documented. While intravascular imaging (IVI) improves percutaneous coronary intervention (PCI) outcomes, its potential sex-specific benefits remain unclear. Objectives: The purpose of this study was to determine sex differences in adverse cardiovascular events in coronary artery disease patients undergoing PCI with IVI guidance vs angiography alone. Methods: Systematic review of PubMed, Scopus, and Cochrane databases was conducted to identify randomized controlled trials comparing major adverse cardiovascular events (MACE) in men and women with coronary artery disease (presenting with acute or chronic coronary syndrome) undergoing IVI-guided vs angiography-guided PCI. Risk ratios (RRs) with 95% CIs were calculated using random-effects models. Results: Eight randomized controlled trials, comprising 14,812 patients (76.1% men and 23.9% women) were included. IVI-guided PCI significantly reduced MACE in both men (RR: 0.69; 95% CI: 0.58-0.81; P < 0.001) and women (RR: 0.64; 95% CI: 0.49-0.82; P < 0.001) compared with angiography alone (Pinteraction = 0.62). Intravascular ultrasound–guided PCI reduced MACE in men and women compared with angiography alone (Pinteraction = 0.86). Optical coherence tomography–guided PCI reduced MACE in men but not in women compared with angiography alone (Pinteraction = 0.86). Conclusions: Despite the underrepresentation of women in IVI-guided PCI trials, this meta-analysis demonstrates that IVI-guided PCI confers a comparable reduction in MACE for both men and women, suggesting its potential to mitigate the long-standing sex-specific disparities in coronary intervention outcomes and supports its broader implementation in clinical practice.